1985
DOI: 10.1002/bbpc.19850891009
|View full text |Cite
|
Sign up to set email alerts
|

Small Angle Neutron Scattering on Nematic Lyotropic Liquid Crystals

Abstract: A solution of 30% by weight of the tetramethylammonium salt of the perfluorononanoic acid (TMPFN = C8F17COON(CH3)4) in D2O forms a nematic phase in the temperature range between 32 and 37°C. The nematic phase was aligned and cooled down to 25°C in a magnetic field of 1.63 and 1.26 T. The structure of the aligned sample was studied with small angle neutron scattering (SANS) at different temperatures. In the liquid crystalline phase first and second order Bragg‐peaks were observed. This phase consists mainly of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…For neutrons the scattering length densities for tail and head groups are both nearly equal and different from go-The diameter of N(CH3)4 is around 0.54 nm. 4 With this value we expect for neutrons to see a thickness of the lamellae of «3.7 nm, a value which is comparable to the measured one.…”
Section: Results For the Isotropic Phasesupporting
confidence: 73%
See 1 more Smart Citation
“…For neutrons the scattering length densities for tail and head groups are both nearly equal and different from go-The diameter of N(CH3)4 is around 0.54 nm. 4 With this value we expect for neutrons to see a thickness of the lamellae of «3.7 nm, a value which is comparable to the measured one.…”
Section: Results For the Isotropic Phasesupporting
confidence: 73%
“…For AV a value of 0.533 nm3 was used. 4 For the calculation of the form factor we analyzed two models.…”
Section: Results For the Isotropic Phasementioning
confidence: 99%
“…Tiddy et al. observed the formation of a hexagonal H 1 phase, an intermediate phase, and a lamellar L α phase for ammonium and lithium perfluorooctanoate. A nematic N D phase and lamellar L α phase were found for cesium perfluorooctanoate and ammonium perfluorononanoate observed the existence of a cubic phase for perfluoroheptanoic acid, its salts, and ethoxylated amides.…”
Section: Introductionmentioning
confidence: 96%
“…Sometimes it was found that a discotic nematic phase existed intermediate between the isotropic and lamellar phases . The lack of cubic and hexagonal phases is explained by the aggregation of the disk-shaped micelles, which already form a lamellar phase at small concentrations . Recently, we have shown that perfluorooctadecanoic acid forms monodispere thin disklike micelles at small concentrations (10 -3 to 10 -4 mol/L) .…”
Section: Resultsmentioning
confidence: 99%